1974
DOI: 10.1021/ja00831a008
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of .alpha.,.alpha.'-bis(diazo)ketones

Abstract: The synthesis and decomposition of 2,6-bis(diazo)cyclohexanone (1) and 1,3-bis(diazo)-l ,3-diphenylpropan-2-one (4) are reported. Cyclopropenones are established as intermediates in the photolytic decompositions. Thermal decomposition of 4 catalyzed by silver oxide and cuprous chloride also involves formation of 1,3-diphenylcyclopropenone. On the other hand, uncatalyzed thermal decomposition of 4 leads to 2,5-diphenyl-3,4-diazacyclopentadienone whose formation represents a novel electrocyclic ring closure. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…[289] Minor amounts of β, γ-unsaturated esters and of β-alkoxy esters were also detected. [290] Irradiation of 1,3-diazo-1,3-diphenylpropan-2-one (382), using monochromatic light at 436 nm, resulted in the isolation of diphenylcyclopropenone (379, R ϭ Ph) whereas at shorter wavelengths diphenylacetylene (380, R ϭ Ph) was obtained. [290] Matrix isolation proved to be helpful in elucidating the reaction mechanism.…”
Section: Reactions With Diazo Compounds and Carbenesmentioning
confidence: 99%
See 1 more Smart Citation
“…[289] Minor amounts of β, γ-unsaturated esters and of β-alkoxy esters were also detected. [290] Irradiation of 1,3-diazo-1,3-diphenylpropan-2-one (382), using monochromatic light at 436 nm, resulted in the isolation of diphenylcyclopropenone (379, R ϭ Ph) whereas at shorter wavelengths diphenylacetylene (380, R ϭ Ph) was obtained. [290] Matrix isolation proved to be helpful in elucidating the reaction mechanism.…”
Section: Reactions With Diazo Compounds and Carbenesmentioning
confidence: 99%
“…[290] Irradiation of 1,3-diazo-1,3-diphenylpropan-2-one (382), using monochromatic light at 436 nm, resulted in the isolation of diphenylcyclopropenone (379, R ϭ Ph) whereas at shorter wavelengths diphenylacetylene (380, R ϭ Ph) was obtained. [290] Matrix isolation proved to be helpful in elucidating the reaction mechanism. Irradiation (Ͼ 274 nm) of 381 in argon at 8 K gave first diazoketene 376 and then cyclopropenone 379 (both with R---R ϭ (CH 2 ) 4 , IR detection).…”
Section: Reactions With Diazo Compounds and Carbenesmentioning
confidence: 99%
“…The two diastereomers erythro-8 (like) and threo-8 (unlike) were identified by comparison of their 1 H NMR spectrum with that of the analogous erythro and threo methyl 2,3-diphenyl-3-methoxypropionate, 26 and other related compounds. 27 The higher coupling constant in the CH-CH system (10.4 vs 9.6 Hz) and the higher chemical shift of the methoxy group (3.22 vs 3.07 ppm) are in agreement with the threo configuration.…”
Section: Reaction Of Methyl P-bromophenyldiazoacetate With Benzyl Metmentioning
confidence: 99%
“…Hence a four-step radical mechanism for conversion of 20 to 16 is probable but a four-step heterolytic mechanism or a combination of both cannot be ruled out. Trost et al (12) observed the formation of 16 from the bisdiazoketone 27 and proposed a mechanism in which 27 is converted to 1 and further 27 reacts with 2 moles of 1 with elimination of 2 moles of N,. This mechanism may still be correct provided 27 is present but this current work reveals an alternative route which does not require reaction of 27 with 1.…”
Section: Cycloadditions Of the Diazacyclopentadienone ( I )mentioning
confidence: 99%